Model Development Strategy for Improved Quality of Private Higher Education that Manage Diploma Program through the Implementation of Good University Governance - Juni Priansa, Donni; Widodo, Teguh; ., . (International Journal of Engineering and Technology, 2019)
Indonesia's competitiveness ranking based on the Global Competitiveness Index (GCI) has not been so encouraging, especially of higher education. This study aims to analyze how the governance and quality of private universities tha manage diploma program; and to analyze the influence of good university governance on the quality of private universities, partially and simultaneously. This study is a descriptive-verification with design research is causality and cross-sectional. The population in this study is a Private Higher Education that manages diploma program. Where the unit sample is a lecturer. Data analysis techniques used in this research is path analysis. The results of this study indicate that the governance descriptive colleges included in the classification of a high score. In addition, the quality of higher education are in a high classification. In the verification results show that the good university governance has positive and significant impact on the quality of private higher education, either partially or simultaneously. These findings illustrate that the private higher education needs to improve its governance through the aspects of transparency, accountability, responsibility, independence and fairness.Â Â
Keywords: Higher Education Governance; Quality Higher Education